PENGARUH VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN ANAK TENTANG PENTINGNYA MENGONSUMSI BUAH DAN SAYUR DI SDN SERANGAN KOTA YOGYAKARTA: PENGARUH VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN ANAK TENTANG PENTINGNYA MENGONSUMSI BUAH DAN SAYUR DI SDN SERANGAN KOTA YOGYAKARTA - Fitri Handayani; Khristina Dias Utami; Sekar Dwi Safitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2026)
Background : School-aged children aged 7–12 years experience rapid growth and development that require adequate nutritional intake, including fruits and vegetables. However, fruit and vegetable consumption among Indonesian children remains low. Lack of consumption may increase the risk of vision problems, fatigue, mouth ulcers, and bleeding gums. One factor influencing children’s consumption behavior is limited knowledge regarding the importance of fruits and vegetables. Animated video media are considered attractive and easy to understand, making them suitable for improving children’s knowledge. Preliminary studies at SDN Serangan Kota Yogyakarta showed that students had limited understanding regarding the importance of consuming fruits and vegetables. Objective : To determine the effect of animated video education on children’s knowledge regarding the importance of consuming fruits and vegetables at SDN Serangan Kota Yogyakarta. Methods : This study used a quasi-experimental design with a one-group pretest-posttest approach. The research was conducted at SDN Serangan Kota Yogyakarta from September 2024 to June 2025. The sample consisted of 35 students in grades III–VI selected using a total sampling technique. Data collection was conducted using a knowledge questionnaire consisting of 22 questions covering the definition, types, benefits, and impacts of inadequate fruit and vegetable consumption. The questionnaire had been tested for validity and reliability, with a Cronbach’s Alpha value of 0.834. Knowledge scores were categorized into low, moderate, and good levels. The intervention used an animated educational video developed by the researcher containing information on the benefits of fruits and vegetables, recommended consumption, and the effects of inadequate intake. The video was shown twice on the same day. Data were analyzed using the Marginal Homogeneity test. Result : Before the intervention, 21 students (60.0%) had low knowledge levels, 8 students (22.9%) had moderate knowledge, and 6 students (17.1%) had good knowledge. After the intervention, knowledge levels improved, with 33 students (94.3%) categorized as having good knowledge and 2 students (5.7%) having moderate knowledge. The Marginal Homogeneity test showed a p-value of <0.001, indicating a significant effect of animated video education on children’s knowledge regarding the importance of consuming fruits and vegetables. Conclusion : Animated video-based education effectively improved elementary school students’ knowledge regarding the importance of consuming fruits and vegetables. Animated videos can be used as an engaging and effective educational medium to support nutrition education programs in schools and encourage healthier eating behaviors among children.